Syntheses, structures, luminescence, NMR spectra and terahertz time-domain spectroscopy of nine lanthanide triflate complexes of tetrakis(O-isopropyl)methylenedisphosphonate with a L:Ln ratio of 4:1. (17th February 2015) - Xu, Shan; Liu, Min; Yang, Yu-Ping; Jiang, Yu-Han; Li, Zhong-Feng; Jin, Qiong-Hua; Wang, Xin; Xue, Xiao-Nan
Graphical abstract: Nine lanthanide complexes with a high L:Ln ratio (4:1), [LnL4 ](OTf)3 (1 –8 ) (L = tetrakis( O -isopropyl)methylenediphosphonate, OTf = SO3 CF3, Ln = Ce, Pr, Nd, Sm, Eu, Gd, Dy, Yb) and [DyL4 ](OTf)3 ·DMF (9 ) have been synthesized in air. These complexes were characterized by elemental analyses, IR spectra, single-crystal X-ray diffraction analysis, luminescence, NMR spectra and terahertz time-domain spectroscopy (THz-TDS). Abstract: Nine lanthanide complexes with a high L:Ln ratio (4:1), [LnL4 ](OTf)3 (1 –8 ) (L = tetrakis( O -isopropyl)methylenediphosphonate, OTf = SO3 CF3, Ln = Ce, Pr, Nd, Sm, Eu, Gd, Dy, Yb) and [DyL4 ](OTf)3 ·DMF (9 ) have been synthesized through easy and effective methods in air. Each complex was synthesized by the reaction of lanthanide triflate with the L ligand in a solvent mixture (acetonitrile and DMF for1 –8, dichloromethane and DMF for9 ). The above complexes, except for complex9, were synthesized in the presence of 1, 10-phenanthroline. The title complexes were characterized by elemental analyses, IR spectra, single-crystal X-ray diffraction analysis, luminescence, NMR spectra and terahertz time-domain spectroscopy (THz-TDS). Structure analysis shows that complexes1 –9 consist of one cation [LnL4 ] 3+ and three triflate anions OTf - . Complexes1 –8 crystallized in the orthorhombic system, space group Pbcn, whereas complex9 belongs to the space group I 222. The cationic [LnL4 ] 3+ fragments in complexes1 –8 are self-assembled to construct 2D layers with a (8·2·8·4) net topology by hydrogen bonding interactions. The OTf − cations in9 are attached directly to the [DyL4 ] 3+ cations to form a 2-fold hydrogen-bonded three-dimensional (3D) cage structure framework. Solid luminescence of complex5 displays the characteristic bands of Eu 3+, due to a long emission lifetime (4.04 ms of 5 D0 ) and high absolute emission quantum yield (53.30%). Terahertz (THz) time-domain spectroscopy of the complexes was also studied.